The imposition of administrative sanctions in the form of interest on Article 25 Income Tax from the perspective of justice - Sumarno, Sumarno (Indonesian Journal of Multidisciplinary Science, 2025)
The research contributes to the understanding of the legal implications of interest sanctions on Income Tax installments under Article 25 of Law Number 7 of 1983, as amended by Law number 7 of 2021 concerning the Harmonization of Tax Regulations (as prepaid tax). The study aims to explore the relationship between these sanctions and the principles of justice for taxpayers. The research method used in this study is normative legal research, focusing on literature materials or secondary data. The study relies on library materials, aiming to explore legal principles, systematics, and synchronization, while also referring to the legal norms outlined in relevant laws and regulations. This study is significant as it addresses the balance between enforcing tax compliance through interest sanctions and ensuring fairness in the tax system, ultimately providing insights that could inform policy adjustments and enhance taxpayer rights.